Expression of KRT7 and WT1 differentiates precursor lesions of Wilms’ tumours from those of papillary renal cell tumours and mucinous tubular and spindle cell carcinomas - Szponar, Adrianna; Kovacs, Gyula (Virchows Archiv, 2012)
Wilms’ tumours (WT) and adult papillary renal cell tumours (pRCT) are associated with precursor lesions of embryonic origin. The aim of this study was to analyse the expression of WT1, KRT7, KRT8, KRT18 and KRT19 genes by immunohistochemistry in 74 precursor lesions associated with WTs, pRCTs and mucinous tubular and spindle cell carcinomas (MTSCC). All precursor lesions associated with Wilms’ tumours were positive for WT1, whereas all precursor lesions in pRCT and MTSCC-bearing kidneys were negative. None of the WT-associated lesions were positive for KRT7, but 69-80% of lesions associated with pRCTs and MTSCCs were positive for KRT7. KRT8, KRT18 and KRT19 were found to be expressed in 80-100% of all types of precursor lesions. Our findings indicate that the precursor lesions analysed in this study are committed in an early stage of cellular differentiation to the development of either Wilms’ tumours or papillary RCTs and MTSCCs.